STUDI TENTANG KEADAAN SANITASI DI RUANG RAWAT INAP RUMAH SAKIT UMUM DAERAH KOTA MEDAN TAHUN 2016 - MARLINA RAJAGUKGUK (LP2MTBM MAKARIOZ, 2019)
The hospital is facility health efforts in conducting health services and can serve as a health education and research. One cause considerable role in creating the conditions that the hospital is convenient for visitors be seen of hospital sanitation. Sanitation is a hospital surveillance efforts various environmental factors such a physical, chemical and biological at the hospital, which cause or may cause adverse effects on physical health, spiritual and social welfare for staff, patients, visitors and the community around the hospital. Regional General Hospital (Hospital) Medan regency is a regional hospital that has been established since 1963, where the hospital is classified as type C. The result was overview of each sanitary conditions in inpatient wards of first grade unit, second grade unit and third grade unit: water supply in the inpatient first grade unit, second grade unit and third grade unit (score = 9; category was good) , solid waste disposal (score = 8; category was good), waste water disposal facilities for second grade unit and third grade unit (score 8; category was good) and for and third grade unit (score 6; category was moderate). Human Excreta disposal facilities in the first unit and second grade unit (score = 8; category was good), third grade unit (score of 6; category was moderate).The sanitation facilities condition in inpatient room at RSUD Medan for the first class was 100% into good category, second class was 40% and 60% was in a middle category, for third grade 100% was included to middle category.